2018
DOI: 10.3892/br.2018.1128
|View full text |Cite
|
Sign up to set email alerts
|

PLXNA2 identified as a candidate gene by genome-wide association analysis for mandibular prognathism in human chondrocytes

Abstract: Abstract. In a previous genome-wide association study, plexin A2 (PLXNA2) was suggested as one of the candidate genes for mandibular prognathism. PLXNA2 encodes plexin A2, a member of the plexin-A family of semaphorin co-receptors. Semaphorin 3A (sema3A) exerts an osteoprotective effect. However, to the best of our knowledge, there have been no previous studies examining the role of sema3A or plexin A2 on human chondrocytes. The objectives of the present study were to examine the function of sema3A and its rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Plexin A2 is also expressed in human chondrocytes where it is believed to bind with semaphorin 3A, a secreted protein that is expressed by osteoblasts, and induce osteoblastic differentiation, the acceleration of cell growth, and the accumulation of extracellular matrices of chondrocytes (Gomez et al, 2005; Hayashi et al, 2012; Kajii et al, 2018). Genome‐wide association study performed on 240 Japanese patients with mandibular prognathism suggested PLXNA2 as a susceptibility locus (Kajii et al, 2018). Possibly reinforcing the role of PLXNA2 in jaw malformations, our study describes an obtuse mandibular angle and a mild overbite shared by the index in Family 1 and the index of Family 2.…”
Section: Discussionmentioning
confidence: 99%
“…Plexin A2 is also expressed in human chondrocytes where it is believed to bind with semaphorin 3A, a secreted protein that is expressed by osteoblasts, and induce osteoblastic differentiation, the acceleration of cell growth, and the accumulation of extracellular matrices of chondrocytes (Gomez et al, 2005; Hayashi et al, 2012; Kajii et al, 2018). Genome‐wide association study performed on 240 Japanese patients with mandibular prognathism suggested PLXNA2 as a susceptibility locus (Kajii et al, 2018). Possibly reinforcing the role of PLXNA2 in jaw malformations, our study describes an obtuse mandibular angle and a mild overbite shared by the index in Family 1 and the index of Family 2.…”
Section: Discussionmentioning
confidence: 99%
“… 30 The interaction of two proteins may suppress the expression of parathyroid hormone-related peptide receptor 1 (PTH-R1) in human proliferative chondrocytes. 31 This is significant because the parathyroid hormone-related protein and its receptor PTH-R1 play a crucial role in regulating chondrocyte proliferation, differentiation, and apoptosis. 32 As most chondrocytes in the mandibular condylar cartilage undergo programmed death, the cartilage matrix is replaced by bone through endochondral ossification, ultimately forming the mandibular condyle.…”
Section: Discussionmentioning
confidence: 99%
“…A missense mutation in BMP3 has been identified as a major contributor to brachycephaly [ 31 ], and a repeat expansion of the RUNX2 gene has been correlated with snout dorsiflexion and midface length in dogs [ 29 ]. Recently, Kajii et al [ 40 ] suggested that PLXNA2 may be a candidate gene for mandibular prognathism since its mutation can delay the early termination of condylar growth. According to this, association of PLXNA2 with SHM could be explained by affecting CCJ and/or vertebral column bone formation, disturbing CSF flow and consequently inducing the formation of syringes.…”
Section: Discussionmentioning
confidence: 99%